2022
DOI: 10.3390/s22218085
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly Detection in Industrial IoT Using Distributional Reinforcement Learning and Generative Adversarial Networks

Abstract: Anomaly detection is one of the biggest issues of security in the Industrial Internet of Things (IIoT) due to the increase in cyber attack dangers for distributed devices and critical infrastructure networks. To face these challenges, the Intrusion Detection System (IDS) is suggested as a robust mechanism to protect and monitor malicious activities in IIoT networks. In this work, we suggest a new mechanism to improve the efficiency and robustness of the IDS system using Distributional Reinforcement Learning (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…adv. trained anomaly detection for CRNs [101] Hierarchical anomaly detection for data aggregation & privacy preservation [102] Anomaly detection by learning minority data classes and data augmentation [103] Efficient and robust intrusion detection for IIoT [104] Cognitive Radio Networks…”
Section: Pla and Adversarial Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…adv. trained anomaly detection for CRNs [101] Hierarchical anomaly detection for data aggregation & privacy preservation [102] Anomaly detection by learning minority data classes and data augmentation [103] Efficient and robust intrusion detection for IIoT [104] Cognitive Radio Networks…”
Section: Pla and Adversarial Trainingmentioning
confidence: 99%
“…By learning minority data classes and generating augmented data, their proposed models outperformed other anomaly detection models in various performance metrics. Likewise, Benaddi et al [104] suggested a mechanism to improve the efficiency and robustness of intrusion detection systems in Industrial IoT networks using distributed RL and GANs. Their proposed models outperformed the standard RL models in various performance metrics.…”
Section: Anomaly and Attack Detectionmentioning
confidence: 99%
“…The researchers of [27] used dynamic features to produce adversarial attacks against black-box malware classifiers and compared the results of using RL and GAN techniques independently. In the field of industrial IoT, Benaddi et al [43] focused on anomaly detection in Intrusion Detection Systems (IDS) using Distributional Reinforcement Learning and GAN. Phan et al [28] proposed an evasion method for black-box malware detectors to evaluate the effectiveness of RL and its combination with GAN, however the focus of their research work is only the comparison between both approaches and did not consider recent state-of-the-art evasion methods in their result analysis.…”
Section: B Malware Evasion Techniquesmentioning
confidence: 99%
“…The IoT is a network of sensors and computational devices that work together to solve problems and provide innovative features [1]. The IoT is a collection of physical objects-"things"-embedded with sensors, apps, and other technology for connecting and transmitting data with other devices and systems through the internet [2][3][4].…”
Section: Introductionmentioning
confidence: 99%